Time Domain Distortion Estimation and Correction Using Sample Shifting Procedure - Cirulis, R.; Greitans, M.; Hermanis, E. (Elektronika ir Elektrotechnika, 2013)
A new method is presented to estimate and compensate sampling instrument’s time base distortion. Method requires periodic test signal. Presented method also provides an algorithm to eliminate time base distortion. Evaluation and correction process is described and illustrated using real acquired test signal. Correction improvement is verified using signal amplitude spectrum comparison. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5654